Child Development after Fetal Exposure to AED - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at the University of Liverpool and the Department of Neurology, Royal Group of Hospitals, Belfast, UK, investigated the early cognitive development of 155 children born to women with epilepsy (WWE) and exposed in utero to the antiepileptic drug, levetiracetam (LEV) or sodium valproate (VPA).